Vedlevande lavar på döda grenar på levande träd i produktionsskog - Livén, Mathias (SLU/Dept. of Ecology, 2010)
Saproxylic lichens in managed forests have less substrate available than in unmanaged forests due to the shortage of dead wood. However, a suitable substrate for these lichens could be dead branches on living trees. To this date, there has not been any systematically collected data about the abundance of dead branches on living trees and the lichens growing on these branches in managed forests. The aim of this study was to see where dead branches were located on living trees of Pinus sylvestris and Picea abies, how large the surface area of these branches was and what lichens grew of wood on these branches. The study was made in Finspång, Sweden, where 11 forest stands of P.sylvestris and P. abies were sampled. Data was collected from ground level to a height of 6 meters. P. sylvestris stands had a larger area of dead wood per dead branch than P. abies stands in the age span of 20-60 years old. In the age span of 61-110 years, P. abies stands had a greater the area of dead wood per dead branch than the P. sylvestris stands. P. sylvestris in the age span older than 110 years old had no dead branches from the ground level up to 6 meters. P. abies stands older than 110 years had the same amount of dead branches and available substrate as the 61-110 age span. Multivariate analysis did not reveal any clear patterns in the composition of the lichen flora between different stands, between the tree species or between heights. Stands of the age span of 20-60 years had very few lichen occurrences and a low number of species found compared to the other age classes.